Evaluation of the seismic performance of masonry buildings of the type “Gaioleiro”, Lisbon (Portugal) - Mendes, N. (2008)
This paper presents the numerical study that aims at the seismic evaluation of the performance of typical Portuguese “gaioleiro” buildings. The numerical modeling was performed with resource to a model of finite elements on 1:3 reduced scale and it was calibrated in agreement with experimental results obtained in the tests done in the LNEC 3D shaking table. With the purpose to define an adequate strategy for seismic performance evaluation nonlinear dynamical analysis with time integration and pushover analyses were carried out. In the dynamic analysis, each earthquake is composed by two uncorrelated artificial accelerograms compatible with design response spectrum of EC8. In the pushover analyses it was considered that the seismic action is simulated through a set of proportional horizontal forces to the mass of structure and to the 1st vibration mode according with the direction in study.